Systematic Literature Review: Gamification in Mathematics Learning - Silvia Indarti; Liyana Sunanto (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the implementation, trends, and research focus of gamification in mathematics learning using a Systematic Literature Review (SLR) approach. Following PRISMA guidelines, articles published between 2015 and 2025 were collected from databases including Google Scholar, DOAJ, Garuda, and Sinta. A total of 100 initial articles were identified, of which 15 met the inclusion criteria and were analyzed in depth. The findings indicate that gamification has a positive impact on students’ motivation, engagement, conceptual understanding, and learning outcomes in mathematics. The dominant research domain is the development of gamification-based learning media, such as interactive applications, e-modules, and electronic worksheets, often designed using the ADDIE model. Other research areas include pedagogical impact, which highlights improvements in students’ participation, enjoyment, and creative thinking, and technology integration, addressing challenges related to digital tools, teacher readiness, and infrastructure. Overall, gamification emerges as a promising pedagogical approach that can enhance learning experiences, foster active participation, and support the development of higher-order thinking skills. Despite these benefits, studies on long-term technology integration, sustainable implementation, and alignment with current curriculum frameworks remain limited. Future research is recommended to explore empirical effectiveness, teacher digital competence, sustainable integration of gamified learning, and its potential to promote critical thinking, problem-solving, and creativity in mathematics education.